Meningkatkan Pengetahuan dan Sikap Remaja tentang Pencegahan Anemia melalui Media Tik Tok di SMPN 8 Cibitung - Annisa Khotimah Azzahra; Dea Anggraeni Sapitri; Beatrix Elizabeth; Yulidian Nurpratiwi (Universitas Malahayati, 2026)
ABSTRACT Anemia is a condition where red blood cells and hemoglobin are less than normal, which often occurs in adolescent girls, due to a lack of knowledge and attitudes that support its prevention. Effective education through popular platforms such as Tik Tok was chosen as an attractive approach to raise awareness of anemia prevention. The purpose of the study was to determine the effect of Tik Tok media platform on knowledge and attitude of anemia prevention. This research method is a quasi-experiment, and the population is 130 students of SMPN 8 Cibitung with a sample of 60 8th grade students divided into 30 people for each group. The independent variable is Tik Tok educational media (audio-visual visual), while the dependent variable is knowledge and attitude about anemia prevention. Measurement using pre-test and post-test questionnaires. The results of quantitative data analysis using Paired Sample T-test showed that there was a significant effect on increasing the level of knowledge and attitudes about anemia prevention ρ-value (0.000) 0.05. Independent Sample T-test showed a significant difference ρ-value (0.000) 0.05 between the groups given video and poster education. The conclusion is that there is an effect of using the Tik Tok media platform as education on knowledge and attitudes about preventing anemia in adolescent girls. It is hoped that the results of this study can increase knowledge for adolescent girls at SMPN 8 Cibitung and be used as a reference for handling anemia prevention. Keywords: Adolescent Girls, Anemia, Attitude, Knowledge, Tik Tok. ABSTRAK Anemia adalah kondisi saat sel darah merah dan hemoglobin kurang dari normal, yang sering terjadi pada remaja putri, akibat kurangnya pengetahuan dan sikap yang mendukung pencegahannya. Edukasi yang efektif melalui platform populer seperti Tik Tok dipilih sebagai pendekatan menarik untuk meningkatkan kesadaran pencegahan anemia. Tujuan penelitian guna mengetahui pengaruh media platform Tik Tok pada pengetahuan dan sikap pencegahan anemia. Metode penelitian ini quasi-experiment, serta populasi adalah siswi SMPN 8 Cibitung berjumlah 130 dengan sampel 60 siswi kelas 8 yang dibagi masing-masing untuk setiap kelompok 30 orang. Variabel independen adalah media edukasi Tik Tok (audio-visual visual), sedangkan variabel dependen adalah pengetahuan dan sikap tentang pencegahan anemia. Pengukuran menggunakan kuesioner pre-test dan post-test. Hasil analisis data kuantitatif menggunakan Paired Sample T-test menunjukkan bahwa terdapat pengaruh signifikan terhadap peningkatan tingkat pengetahuan dan sikap tentang pencegahan anemia ρ-value (0,000) 0,05. Independent Sample T-test menunjukkan perbedaan signifikan ρ-value (0,000) 0,05 antara kelompok yang diberikan edukasi video dan poster. Kesimpulan terdapat pengaruh penggunaan media platform Tik Tok sebagai edukasi terhadap pengetahuan dan sikap tentang pencegahan anemia pada remaja putri. Diharapkan hasil penelitian ini dapat menambah pengetahuan bagi remaja putri di SMPN 8 Cibitung dan dijadikan acuan untuk menangani penanggulangan dan pencegahan anemia. Kata Kunci: Anemia , Pengetahuan, Remaja Putri, Sikap, Tik Tok.